Beam-Columns with Finite Deflections - Kalaga, S; Adluri, S. M. R (Journal of structural engineering (New York, N.Y.), 2000)
The large deflection behavior of a uniaxially bent beam-column subject to an eccentrically applied load is investigated. A closed-form expression for the total lateral deflection, including bowing and initial imperfection, is derived by adopting a nonlinear strain-displacement relationship and a sine curve approximation for the lateral deflection. Stability is checked by evaluating the Hessian matrix of the total potential energy. The formulation is validated by applying it to a steel beam-column with an L r ratio of 200. Though not comprehensive, results indicate that it is possible to develop reasonable closed-form solutions for the nonlinear behavior of slender beam-columns.